Gender differences in transdiagnostic domains and function of adults measured by DSM-5 assessment scales at the first clinical visit: a cohort study - Erika F.H. Saunders; Megan Brady; Dahlia Mukherjee; Ritika Baweja; Lauren N. Forrest; Hassaan Gomaa; Dara Babinski; Fan He; Amanda M. Pearl; Duanping Liao; Daniel A. Waschbusch (BMC Psychiatry, 2023)
Abstract Background Measurement-based care has been called for as best practice in psychiatric care and learning health systems and use of transdiagnostic measures was suggested as part of the DSM-5. Our objective is to examine gender differences in first visit socioeconomic, transdiagnostic, and functional characteristics of a dynamic, real-world measurement-based care cohort. Methods Transdiagnostic, functional, and clinical measures were collected from 3,556 patients at first visit in an ambulatory psychiatric clinic. All patients were evaluated at the first visit by board-certified psychiatrists or licensed clinical psychologists. Demographic variables and clinical diagnoses were collected from the Electronic Medical Record. Self-report measures were collected that assessed transdiagnostic symptoms (DSM-5 Level 1 Cross-cutting Measure and Level 2 symptom scales), disability, alcohol use, attention deficit hyperactivity disorder (ADHD) symptoms, depression, anxiety, mania, suicidal thoughts and behaviors, and trauma exposure. Results Men and women did not differ in age, BMI, household income, high school graduation rate, race, or ethnicity, but women were more likely to be formerly married and less likely to have commercial insurance. Compared to men, women reported significantly higher overall psychopathology on the transdiagnostic Level 1 Cross-cutting measure and had higher depression, anxiety, sleep, anger, ADHD combined presentation, and suicidality severity. Women also had higher disability scores than men. However, men reported higher alcohol, tobacco and substance use, and more risky behavior than women. Trauma exposure differed significantly by gender; men reported more exposure to accidents, war-related trauma, serious accidents, and major disasters and women reported more unwanted sexual contact. Conclusions This cross-sectional study of a transdiagnostic, ecologically-valid real-word measurement-based care cohort demonstrates gender differences in socioeconomic factors, trauma exposure, transdiagnostic symptoms, and functioning.